A quality improvement initiative to improve the appropriateness of candidemia management by the implementation of a comprehensive candidemia care bundle at a tertiary care hospital in South India: Results of a quasi-experimental study. Issue 13 (1st April 2022) - Moni, Merlin; Sidharthan, Neeraj; Sudhir, Sangita; Prabhu, Binny; Nampoothiri, Vrinda; James, Jini; Philip, Jeslyn Mary; Thomas, Jisha; Antony, Remya; Mohamed, Zubair Umer; Kumar, Anil; Prasanna, Preetha; et al.
Abstract : Abstract: Management of candidemia in developing countries like India encounters laxity in appropriate clinical management and challenges in terms of healthcare capacity, despite its association with high morbidity and mortality. Our study aims to evaluate the impact of a comprehensive candidemia care bundle implementation on appropriateness of therapy and major clinical outcomes. The single-center, quasi-experimental study conducted at a south Indian tertiary care center included adult patients diagnosed with candidemia. Following a retrospective review of candidemia patients of the pre-implementation period (January 2013–December 2015), the hospital antifungal stewardship team instituted a clinical pharmacist driven comprehensive candidemia care bundle for candidemia patients during the post-implementation period (October 2017–2019) and its impact on appropriateness of antifungal prescriptions and inpatient mortality was evaluated. The study included 175 patients with candidemia, comprising of 103 patients in the pre-implementation period and 72 patients in the post-implementation period. Appropriateness of antifungal prescriptions rose to 65% during post-implementation period from 30% observed in pre-implementation phase ( P  = .0005). The inhospital mortality rate reduced from 40% in the pre-implementation phase to 36% in the post-implementation phase, recording a 10% reduction over 2 years post-implementation ( P  = .26). No significant difference was observed in terms length of stay ( P  = .17). Our study demonstrates the successful implementation of an antifungal stewardship led comprehensive care bundle in a low middle income countries setting. The results of our study will have profound implications in improving the appropriateness of management of candidemia and feasibility of scaling up to wider settings could be explored.